EXPLORING THE FAMILY CONCEPT THROUGH LINGUISTICS - Xalilova Zarnigor Muhammadjon qizi (Web of Journals Publishing, 2024)
This article delves into the intricate interplay between language and the concept of family, aiming to illuminate the multifaceted nature of familial relationships. Drawing upon linguistic theories and methodologies, it investigates how language constructs, reflects, and perpetuates various aspects of family dynamics, including kinship terminology, discourse patterns, and communicative strategies. Through a synthesis of empirical research and theoretical frameworks, this exploration unveils the nuanced ways in which language both shapes and is shaped by familial interactions, shedding light on the cultural, social, and psychological dimensions of the family unit. By interrogating linguistic manifestations of family, this study offers insights into the complexities of human connection and identity within the familial context, ultimately contributing to a deeper understanding of the intricate tapestry of family life.
Keywords: kinship terminology, address forms, family narratives, bilingual and multilingual language practices, the complex dynamics of family life.